Evaluasi Kapabilitas Sistem Informasi Pasien ICU dan HCU Menggunakan COBIT 5 dengan Domain BAI - Erick Fernando; Jullend Gatc; yuhefizar Yuhefizar (Indonesian Society of Applied Science, 2023)
The hospital's Intensive Care Unit (ICU) and High Care Unit (HCU) systems are very important systems and are always used, so it is necessary to know the extent of their performance. Thus, the study aims to provide reference for xyz hospital regarding the condition (performance) of the current ICU and HCU patient systems. COBIT 5 is an information system capability evaluation framework with the build, acquire and implement (BAI) domain. Domain BAI focuses on developing, acquiring, and implementing information systems, applications, and services. It covers the entire IT project life cycle, starting with the planning and requirements gathering phases and continuing through the design, development, testing, and deployment phases. This study also uses qualitative approach with literature studies and quantitative approach for data analysis to measure capability level. Research respondents were heads and staff from the IT, ICU, and HCU divisions. The results of this study describe the level of capability achieved by hospitals in the BAI Domain, with an average score of 3.30 at the established level. This level illustrates that the application of information technology can achieve process results that are in accordance with the wishes of raft xyz management. This stage also illustrates that the xyz hospital has an information technology process that has been standardized thoroughly to achieve all processes. The results of this evaluation can also be guideline for the xyz raft house to make improvements and improve the performance of the ICU and HCU patient systems in meeting the needs of intensively treated patients.